PsycEXTRA Dataset 2000
DOI: 10.1037/e452722008-001
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment and testing orders: Final evaluation report--Home Office research study 212

Abstract: The Research, Development and Statistics Directorate RDS is part of the Home Office. The Home Office's purpose is to build a safe, just and tolerant society in which the rights and responsibilities of individuals, families and communities are properly balanced and the protection and security of the public are maintained. RDS is also a part of the Government Statistical Service (GSS). One of the GSS aims is to inform Parliament and the citizen about the state of the nation and provide a window on the work and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 2 publications
3
60
0
Order By: Relevance
“…Pilot DTTO schemes were introduced in England in 1998 in three pilot sites, with varying degrees of success (Turnbull et al, 2000). Revocation rates differed markedly from 28 per cent in one site to 60 per cent in another and a number of issues were identified that needed to be addressed prior to any national rollout of orders.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pilot DTTO schemes were introduced in England in 1998 in three pilot sites, with varying degrees of success (Turnbull et al, 2000). Revocation rates differed markedly from 28 per cent in one site to 60 per cent in another and a number of issues were identified that needed to be addressed prior to any national rollout of orders.…”
mentioning
confidence: 99%
“…Second, they emphasised the case management role of the supervising officer, who would be responsible for co-ordinating service provision rather than directly providing services. Third, and perhaps most significantly, they included provision for sentencers to take an active role in reviewing the progress of offenders on orders by bringing them back to court on a regular basis (or, alternatively, scrutinising progress through paper-based reviews).Pilot DTTO schemes were introduced in England in 1998 in three pilot sites, with varying degrees of success (Turnbull et al, 2000). Revocation rates differed markedly from 28 per cent in one site to 60 per cent in another and a number of issues were identified that needed to be addressed prior to any national rollout of orders.…”
mentioning
confidence: 99%
“…The initial resistance to the drugs-crime agenda, found in the opinions of drug workers during the DTTOs evaluation (Turnbull, et al, 2000) was not widespread in the opinions of those interviewed for this study. While drug workers recognised the need to help clients "reduce their drug use, or with housing or employment issues" [Graham, Substance Misuse Practitioner] most of them also acknowledged the priority to reduce crime.…”
Section: Achieving Coherence Between Criminal Justice and Drug Treatmmentioning
confidence: 88%
“…Similarly, Weston (2014) argues that the 'reframing' of drug policy has resulted in the articulation of inconsistent messages that may have reinforced the polarised treatment ideologies observed among professionals working with drug users. The implementation of DTTOs encountered many of these difficulties with cultural, ideological and philosophical differences found between treatment and criminal justice staff resulting in fundamental problems around interagency working between the two groups (Turnbull, et al 2000;Hough, et al, 2003). The entrenched institutional interests of the health-oriented agencies around care, health and harm reduction clashed with the coercive and punitive based ethos of the CJS.…”
Section: Introductionmentioning
confidence: 99%
“…This article however, focuses on just one aspect of the 2003 legislation, namely the community supervision of drug misusing offenders. Drug misusers present the probation service with a number of challenges; conventional wisdom suggests that the inevitable escalation in the level of their criminality, combined with their propensity toward a chaotic lifestyle and an inclination toward relapse make them especially vulnerable to falling foul of the terms and conditions of supervision (Turnbull et al 2000).…”
Section: Introductionmentioning
confidence: 99%